De-mystifying the European Union: Reflections on the margins of the conference on the future of the European Union - Bóka, János (The Policies of the European Union from a Central European Perspective, 2022)
The intellectual constructs of communities, especially myths of origin and other myths, play a role not only in interpreting the present but also in shaping plans and strategies for the future. Fortunately, political myths facilitate these processes: they strengthen community cohesion and motivate collective action. Myths are useful as long as they promote intellectual connection with reality rather than isolation from it. But the European Union is a special intellectual construct in the sense that it does not seek to represent or interpret reality, but to transform it. Hence the particular strength of the myths of the European Union, which claim exclusivity both in the face of reality and in the face of political will to the contrary. At present, these myths frame the debate on the future of the European Union – and, at the same time, strictly delimit the discourse that can emerge about its objectives and functioning. This academic work presents and analyses some of the myths of European integration.Keywords: European integration, future of the European Union, myths of the integration